An Analysis of Students’ Needs for Educational Games in Mathematics Learning - Dina Septiyana; Glenda Loisa Katrin; Angre Andes Thofan; Putri Sasalia S. (Journal of Instructional Mathematics, 2026)
The persistent gap between conventional mathematics instruction and students' digital-era learning needs demands a fundamental reimagining of instructional media in junior high schools. This study used students perceptions as data, including the effectiveness of current mathematics learning, the level of technology use, and the obstacles they experienced while learning mathematics at junior high schools in Palangka Raya City. Data were collected through a needs questionnaire that focused on learning motivation, the availability of learning media, and students’ views on the use of games as learning aids. The analysis showed that most students needed learning media that were more engaging, interactive, and able to help them visualize mathematical concepts more clearly. Further findings indicated that students’ difficulties in understanding mathematical concepts were related to the teaching methods used by teachers and the limited use of digital learning media in the classroom. Integrating educational games could provide visual, contextual, and interactive experiences to support deeper understanding. These results strengthen the evidence that game-based learning can increase student engagement and encourage a more meaningful learning process. Addressing students' learning needs through digital instructional media, particularly educational games, is fundamental to advancing meaningful mathematics learning in secondary education.